66 Significance of Percutaneous Biopsy in the Clinical Management of Renal Masses. (12th October 2021) - Cheah, W; Marques, S D B; Bhuvanagiri, A; Kailasa, A; Thangavelu, M; Alexandrou, K; Kannan, S
Abstract: Aim: Percutaneous renal mass biopsy is increasingly used in the management of renal masses. The objective of our study was to determine the significance of percutaneous renal mass biopsy and its impact on clinical management. Method: Retrospective study of all patients who had image guided percutaneous renal mass biopsy health-board wide from April 2011 to April 2019. Renal mass biopsies were performed for either a localised or metastatic renal mass. Results of the renal biopsies were compared to final diagnosis to determine diagnostic accuracy measured by sensitivity, specificity, negative predictive value and positive predictive value. Results: Out of 429 patients who had a renal biopsy, 91 patients- 55 males (61%) and 36 females (39%) were included in the final analysis. The mean age of the study population was 66 years (range 46-87). Renal mass biopsies were performed using coaxial 18-gauge core needle technique. We categorised patients into two groups (metastatic renal masses and localised renal mass). Sixty-eight patients had biopsies for metastatic disease and 23 patients had biopsies for a localised renal mass. In the localised disease group, the sensitivity was 100%, positive predictive value was 82% (95% CI, 48.2-97.7%) and the negative predictive value was 100% (95% CI, 66.4-100%) (Clopper Pearson Method). For patients with metastatic renal mass the positive predictive value was 83%. Conclusions: Percutaneous renal mass biopsy may have a role for metastatic renal cancers that require targeted therapy and localised masses that require curative treatment.